Psychological Inflexibility and Loneliness Mediate the Impact of Stress on Anxiety and Depression Symptoms in Healthcare Students and Early-Career Professionals During COVID-19 - Bonilla-Sierra, Patricia; Manrique-G, Alexis; Hidalgo-Andrade, Paula; Ruisoto, Pablo (Frontiers in Psychology, 2021)
Background: The current mental health state of healthcare professionals and students during the COVID-19 pandemic in Ecuador remains understudied and how to improve their mental health is a challenge. Objective: This study aimed to explore the anxiety and depressive symptomatology among healthcare students and professionals in Ecuador and to examine the role of psychological inflexibility, loneliness, and psychological stress as predictors of anxiety and depression symptoms. Methods: A total of 191 undergraduate and graduate healthcare students in clinical practice (early-career healthcare professionals) in Ecuador were surveyed between January and March 2021 using standardized measures of psychological stress (PSS), psychological inflexibility (AAQ), loneliness (UCLA), alcohol consumption (AUDIT-C), and anxiety and depressive symptomatology (PHQ). Macro Process for SPSS (models 4 and 7) were used to test mediation effects. Results: Alcohol consumption varied between men and women and anxiety and depression symptomatology was generally low among the sample. Psychological inflexibility and loneliness mediated the impact of stress on anxiety and depressive mood in participants, regardless of gender and previous personal history of COVID-19. Discussion: Implications of psychological inflexibility and the prevention and coping with stress in healthcare professionals during COVID-19 are further discussed.